2009
DOI: 10.1103/physrevb.80.155301
|View full text |Cite
|
Sign up to set email alerts
|

Gate-inducedg-factor control and dimensional transition for donors in multivalley semiconductors

Abstract: The dependence of the g factors of semiconductor donors on applied electric and magnetic fields is of immense importance in spin-based quantum computation and in semiconductor spintronics. The donor g-factor Stark shift is sensitive to the orientation of the electric and magnetic fields and is strongly influenced by the band-structure and spin-orbit interactions of the host. Using a multimillion atom tight-binding framework, the spin-orbit Stark parameters are computed for donors in multivalley semiconductors,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 34 publications
6
48
0
Order By: Relevance
“…This effect was partially anticipated by earlier ab initio treatments in Ref. 22, but we improve those predictions with quantitative matching of experiments, and extend them to all donors with a more clear understanding of the underlining physics.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…This effect was partially anticipated by earlier ab initio treatments in Ref. 22, but we improve those predictions with quantitative matching of experiments, and extend them to all donors with a more clear understanding of the underlining physics.…”
Section: Introductionsupporting
confidence: 66%
“…The relative importance of these two kinds of orbital coupling can be preliminarily assessed by comparing the energy differences between the respective unperturbed states to be coupled: the inter-band energy difference involved in the single-valley mechanism is two orders of magnitude larger than the E T 2 − E A1 splitting 43 , which is relevant for valley repopulation. It is thus predicted that the g-factor shifts will be much larger when the valley repopulation effect plays a role, and this has been indeed verified by ab initio calculations in Ge:P 22 . Thus, we limit ourselves to the calculation of the more important spin-orbit Stark shifts induced by valley repopulation, especially since approach relies on a single band approximation which is unable to account for the single valley g-factor shifts.…”
Section: B Spin-orbit Stark Shiftsmentioning
confidence: 63%
“…19), as well as the electronic g factor (g e (E)) (ref. 20), has been calculated within the tight-binding formalism (see Methods). We found that the Stark shift of the g factor is at least an order of magnitude weaker for the 2-P cluster than for 1-P (see Supplementary Note 2).…”
Section: Discussionmentioning
confidence: 99%
“…18 The atomistic configuration interaction method used here goes beyond these approximations to include the Stark effect, large wavefunction overlap and electron-electron exchange and correlations. In this work, we use a large-scale atomistic tight-binding method that describes the crystal as a linear combination of atomic orbitals, and captures the full-energy spectrum of a donor in silicon, including the conduction band valley degrees of freedom, the valley-orbit interaction, 24 the Stark shift of the donor orbitals, 18 and real and momentum space images of the donor obtained by scanning tunnelling microscope experiments. 25 Using the atomistic wavefunctions, we compute the two-electron states of donor and donor clusters in the presence of an electric field from an FCI technique.…”
Section: Methodsmentioning
confidence: 99%